The effect of the thyristor energy router on harmonics - Elena Sosnina; Rustam Bedretdinov; Evgeny Kryukov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Energy routers (ER) are the key equipment of the energy internet that provides control over bidirectional power flows and the voltage level of an electric network. The paper presents the thyristor-powered ER (TER) for an Internet-style medium voltage distribution electric network (6, 10, 20 kV). The developed scheme of the device implements longitudinal and transverse voltage regulation at the ER connection point and it allows changing the power flow and the voltage level in the network. The article is devoted to the study of the harmonic components of voltage introduced into the electrical network by the semiconductor elements of the TER. A mathematical and a computer model and a prototype of an electric network section with a TER have been developed. The studies carried out with the help of the developed models have shown that the device does not significantly distort sinusoidally. The harmonic components factor of the output voltage has acceptable values over the entire range of an effective regulation.